2006
DOI: 10.1103/physrevc.73.024311
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution study of Gamow-Teller transitions from theTz=1nucleusTi46

Abstract: The Gamow-Teller (GT) transition strengths in fp-shell nuclei are important parameters in presupernova models. A high-energy-resolution ( 3 He, t) experiment was performed on the T z = 1 nucleus 46 Ti at 0 • and at an intermediate incident energy of 140 MeV/nucleon for the study of precise GT transition strengths to the final T z = 0 nucleus 46 V. With an energy resolution of 33 keV, individual GT transitions were observed and GT strengths were derived for them up to the excitation energy of 4.5 MeV. The GT st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 58 publications
(138 reference statements)
0
27
0
Order By: Relevance
“…As a result, in the studies of GT excitations on T z = +1 target nuclei 54 Fe [20] and 58 Ni [21] performed up to E x ≈ 13 MeV, it was found that the bump-like structures of GTRs observed in (p, n) studies actually consist of many discrete states excited by GT transitions (GT states). The fragmented GT states were also observed in the studies of the other T z = +1 target nuclei 46 Ti [22] and 50 Cr [23] and in a recent study of the T z = +3/2 nucleus 47 Ti [24].…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…As a result, in the studies of GT excitations on T z = +1 target nuclei 54 Fe [20] and 58 Ni [21] performed up to E x ≈ 13 MeV, it was found that the bump-like structures of GTRs observed in (p, n) studies actually consist of many discrete states excited by GT transitions (GT states). The fragmented GT states were also observed in the studies of the other T z = +1 target nuclei 46 Ti [22] and 50 Cr [23] and in a recent study of the T z = +3/2 nucleus 47 Ti [24].…”
Section: Introductionmentioning
confidence: 53%
“…It is suggested that the fragmentation in this region is caused by the mixing with the sdshell configurations resulting from ground state correlations (see also the discussions in Refs. [22,32]). Note that this effect is not included in our SM calculation, since we assume an inert 40 Ca core.…”
Section: A Gamow-teller Strength Distributionmentioning
confidence: 99%
“…The A dependence of R 2 was systematically studied and a smooth increase in R 2 was observed as A increases [36,37]. A value of R 2 =8.1±0.4 can be deduced for the A = 47 nuclei by quadratically interpolating the experimentally obtained R 2 values for A = 26 [13], 34 [15], 46 [16], 54 [18], 64 [19], 78 [38], 118, and 120 [39]. The resulting B(GT) value obtained for the GT transition to the E x =4.150 MeV, IAS is shown in Table I.…”
Section: Inmentioning
confidence: 99%
“…On the basis of these observations, the strengths of GT transitions starting from the T z = +1, pf -shell nuclei 46 Ti, 50 Cr, 54 Fe, and 58 Ni, and also the T z = +4 nucleus 64 Ni have been intensively studied [11,[16][17][18][19]. The bump-like GTR structures consisting of many fragmented states were observed for nuclei A ≥ 54 but not for the nuclei A ≤ 50.…”
Section: Introductionmentioning
confidence: 99%
“…Fine structures are also reported in pf -shell nuclei 50 Mn, 54 Co, and 58 Cu (T z = 0) [35][36][37][38], 47 V (T z = +1/2) [39], 48 V and 60 Cu (T z = +1) [5,40], 62 Cu (T z = +2) [5], and 64 Cu (T z = +3) [5,41]. However, the GTR structure was not found in 42 Sc (T z = 0) [26] and was not clear in 46 V (T z = 0) [38,42] as well as 44 Sc (T z = +1) [43]. Note that the observed features of the strength distributions and the fragmented GTR structures are distinctively different in these sd-and pf -shell nuclei, showing a marked individuality of their structures (see the discussion in Refs.…”
Section: Almentioning
confidence: 92%